2018
DOI: 10.1002/cne.24376
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the neural stem cell niche in the adult hypothalamus of human, mouse, rat and gray mouse lemur (Microcebus murinus)

Abstract: The adult brain contains niches of neural stem cells that continuously add new neurons to selected circuits throughout life. Two niches have been extensively studied in various mammalian species including humans, the subventricular zone of the lateral ventricles and the subgranular zone of the hippocampal dentate gyrus. Recently, studies conducted mainly in rodents have identified a third neurogenic niche in the adult hypothalamus. In order to evaluate whether a neural stem cell niche also exists in the adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 103 publications
0
98
1
Order By: Relevance
“…Furthermore, Notch signaling through glial cells has been implicated in regulating memory impairments from sleep loss in Drosophila (Miller et al, 2009). Note, however, that a previous immunochemical study of perfused tissue did not see co‐expression of SOX2 with nestin or vimentin in mouse SCN (Pellegrino et al, 2018), whereas we observed about 5% of cells in explant cultures co‐expressing SOX2 and vimentin.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Notch signaling through glial cells has been implicated in regulating memory impairments from sleep loss in Drosophila (Miller et al, 2009). Note, however, that a previous immunochemical study of perfused tissue did not see co‐expression of SOX2 with nestin or vimentin in mouse SCN (Pellegrino et al, 2018), whereas we observed about 5% of cells in explant cultures co‐expressing SOX2 and vimentin.…”
Section: Discussioncontrasting
confidence: 99%
“…Explant cultures prepared from mice of different genetic backgrounds indicated stem‐like SCN cells are not limited to B6 mice and are likely found in other species. A publication that appeared after our work was completed, provided evidence that the adult human SCN contains stem‐like cells, suggesting that this may be a general property of the brain clock (Pellegrino et al, 2018). Studies exploring what factors maintain the immature state of SCN cells are aided by the knowledge that circadian rhythms persist in SPM; interaction between circadian clock components and stem cell‐related genes may provide insight into cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…205,206 Subsequent to these pioneering works, a series of investigations and reviews supported the contention that neurones and glial cells are generated from local NSC in the hypothalamus throughout life. 58,[207][208][209][210][211][212][213][214][215] What is the source of these new neurones? Increasing evidence has shown that tanycytes exhibit NSC properties.…”
Section: Neur Al S Tem Cell Propertie S Of Tanyc Y Te Smentioning
confidence: 99%
“…Most recently, Pellegrino et al have reported on a comparative study of the neural stem cell niche in the adult hypothalamus of human, mouse rat and gray mouse lemur using a panel of 5 neural stem/progenitor cell (NPCs)-specific markers including Sox2, Nestin, Vimentin, GLAST and GFAP [55]. Their data suggest that unlike the mouse, rat and the gray mouse lemur, adult human hypothalamus contains 4 different NPC cell types express including a ribbon of small stellate cells lining the third ventricular wall, ependymal cells, tanycytes and a population of small stellate cells in the suprachiasmatic nucleus.…”
Section: Do Tanycytes Mimic Stem Cells?mentioning
confidence: 99%